Islam, Bahasa Arab, dan Pengaruhnya terhadap Bahasa Makassar - Baso, Yusring Sanusi (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2018)
This study describes the influence of Islam and Arabic on the Makassarese language. The method used in this study is library research. Various literatures were collected to obtain data and facts. These data are collected, sorted and selected and then analyzed to answer two primary issues, namely the influence of Islam and the influence of Arabic on the Makassarese language. The results of the study showed that the Islamic religion influenced the contents of poetry and song in the Makassarese language. The vocabulary from Arabic absorbed into the Makassar language experiences several typologies, including vocabulary absorption and vocabulary enrichment in the Makassarese language. This word absorption from Arabic also includes sound adjustments in Makassarese language. In addition to that, there are words found in Arabic words whose meaning absorbed in Makassarese language not in terms of morpholigical absorption but semantical absorption.